2022
DOI: 10.3390/rs14040828
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three Long-Term Satellite-Based Precipitation Estimates against Ground Observations for Drought Characterization in Northwestern China

Abstract: Long-term satellite-based precipitation estimates (LSPE) play a significant role in climatological studies like drought monitoring. In this study, three popular LSPEs (Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks–Climate Data Record (PERSIANN-CDR), Rainfall Estimates from Rain Gauge and Satellite Observations (CHIRPS) and Multi-Source Weighted-Ensemble Precipitation (MSWEP)) were evaluated on a monthly scale using ground-based stations for capturing drought event c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
1
14
1
Order By: Relevance
“…Finally, the bias adjustment for precipitation estimates has been applied by matching the Global Precipitation Climate Project (GPCP) Monthly Product Version 2.2 (GPCPv2.2) at 2.5 • resolution. The spatial coverage of this precipitation product is 60 • N-60 • S and its highest temporal resolution could reach up to 3 h [33]. Where G stands for the rain gauge, S is for satellite, Re is for reanalysis, Ra means radar, and NRT stands for near-real-time.…”
Section: Satellite-based Precipitation Productmentioning
confidence: 99%
“…Finally, the bias adjustment for precipitation estimates has been applied by matching the Global Precipitation Climate Project (GPCP) Monthly Product Version 2.2 (GPCPv2.2) at 2.5 • resolution. The spatial coverage of this precipitation product is 60 • N-60 • S and its highest temporal resolution could reach up to 3 h [33]. Where G stands for the rain gauge, S is for satellite, Re is for reanalysis, Ra means radar, and NRT stands for near-real-time.…”
Section: Satellite-based Precipitation Productmentioning
confidence: 99%
“…The Thornthwaite (TW) ( Thornthwaite, 1948 ) and P-M ( Monteith, 1965 ) formulas were commonly used to calculate the PET in the SPEI estimation. The SPEI calculated based on TW formula was easily to implement, while it may indicate excessive dry conditions due to the influence of temperature, under the significantly increased temperatures in recent years ( Zhang et al., 2017 ; Nouri and Homaee, 2020 ; Guo et al., 2022 ). Compared to the TW formula, which only considers temperature, the P-M formula considered variety of meteorological factors, which are more complex, and is generally more consistent with actual evapotranspiration ( Jensen et al., 1990 ), specially it enable to describe the regions influenced by aerodynamic factors ( Liu and Jiang, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the run course theory (Yevjevich, 1967), this study identified drought events and quantitatively analyzed the drought characteristics of drought events, as shown in Figure 3. The paper only focuses on drought events with a long duration and a high drought peak: drought (SPI<0) for 3 consecutive months or more and the peak value less than −1.0 (Guo et al, 2022). The time when SPI starts to be negative and recovers to be positive are defined as the beginning and end time of drought event respectively, and the period is the duration of drought (Formula 10).…”
Section: Identification and Quantitative Characterization Of Drought ...mentioning
confidence: 99%
“…Among them, the North and South regions passed the significance level test of 0.05, and the change trend of the West and East only passed the significance level test of 0.1. Since 2000, the overall wetting trend has been intensified, which may be due to the enhanced water vapor transport from high latitudes in the northern Hemisphere with the global warming since the 21st century, and the "three-stage water vapor relay transport" from the tropical Indian Ocean and Arabian Sea to the Central Asian mountains through the western Indian Ocean, the southern Arabian Peninsula and Central Asia (Guo et al, 2022).…”
Section: Analysis Of Drought Trendmentioning
confidence: 99%